Quantitative risk assessment of gas leakage and explosion accidents and its security measures in open kitchens. (December 2021) - Cen, Kang; Song, Bin; Jiao, Wenling; Yu, Wuge; Liu, Tianjie; Zhang, Hanyue; Du, Juan
Highlights: A gas leakage and explosion experiment platform like a kitchen was constructed. A quantitative risk assessment methodology is developed for open kitchens. The simulation results are in good agreement with the experimental results. The integrated risk in open kitchens is greater than that in traditional kitchens. The active and passive security measures are proposed for open kitchens. Abstract: In this study, a quantitative risk assessment methodology is developed for gas leakage and explosion accidents in open kitchens. Meanwhile, the corresponding security measures are investigated. The physical and computational model of a typical open kitchen and the corresponding traditional kitchen is firstly developed, using CFD code FLACS, respectively. Based on the similarity principle, a small scale low-pressure natural gas leakage and explosion experiment platform like a kitchen was constructed to validate the accuracy of CFD model. Subsequently, gas leakage and dispersion behavior is performed to analyze the gas concentration distribution. Meanwhile, a time-of-exposure model is introduced to calculate the overall ignition probability during the whole gas leakage and dispersion process. And then, the explosion simulation with a real inhomogeneous flammable gas cloud is carried out to analyze the overpressure distribution. In addition, the maximum weighted average overpressure is estimated accurately. According to the overall ignition probability and the maximum weighted average overpressure, the integrated risk caused by gas leakage and explosion accidents is assessed. Furthermore, the active and passive security measures are investigated to reduce the integrated risk in open kitchens. This methodology and its security measures are applied to a typical open kitchen, located in Harbin, China. The results show that the simulation results reproduced by the CFD model are in good agreement with the experimental results. The explosion accident probability in open kitchens is much higher than that in traditional kitchens, whereas the explosion accident consequences in open kitchens are less than that in traditional kitchens. The integrated risk in open kitchens is greater than that in traditional kitchens. These achievements provide an effective theoretical guidance and technical support for safety gas supply design of open kitchens.